Versatile shaper-assisted discretization of energy–time entangled photons - B Bessire; C Bernhard; T Feurer; A Stefanov (New Journal of Physics, 2014)
We demonstrate the capability to discretize the frequency spectrum of broadband energy–time entangled photons by means of a spatial light modulator to encode qudits in various bases. Exemplarily, we implement three different discretization schemes, namely frequency bins, time bins and Schmidt modes. Entangled qudits up to dimension d = 4 are then revealed by two-photon interference experiments with visibilities violating a d -dimensional Bell inequality.